2005
DOI: 10.1016/j.proci.2004.07.050
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of kerosene combustion in a supersonic model combustor using effervescent atomization

Abstract: Investigation of kerosene combustion in a Mach 2.5 flow was carried out using a model supersonic combustor with cross-section area of 51 mm · 70 mm and different integrated fuel injector/flameholder cavity modules. Experiments with pure liquid atomization and with effervescent atomization were characterized and compared. Direct photography, Schlieren imaging, and planar laser induced fluorescence (PLIF) imaging of OH radical were utilized to examine the cavity characteristics and spray structure. Schlieren ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Despite challenging conditions, laser diagnostic techniques have been used to study high pressure kerosene combustion [30][31][32]. Since preheat and dilution have been shown to alter the heat release characteristics [2,3,6,12], it is essential to investigate the effect of hot product dilution on heat release rate profiles and therefore explore possibilities of experimental markers used to map them.…”
Section: Introductionmentioning
confidence: 99%
“…Despite challenging conditions, laser diagnostic techniques have been used to study high pressure kerosene combustion [30][31][32]. Since preheat and dilution have been shown to alter the heat release characteristics [2,3,6,12], it is essential to investigate the effect of hot product dilution on heat release rate profiles and therefore explore possibilities of experimental markers used to map them.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 It was also shown that a higher level of atomization can be achieved by using effervescent atomization, which can further promote the overall burning of kerosene in a supersonic airflow. 27,28 As discussed earlier, with the use of regenerative cooling the liquid fuel could be vaporized before reaching the fuel injector. Even before the temperature is sufficiently high for the fuel to thermally react, the changes in thermophysical properties of the fuel, from saturated liquid to supercritical fluid, are expected to significantly affect the fuel injection process and the subsequent fuel-air mixing and combustion inside the supersonic combustor.…”
mentioning
confidence: 99%
“…G. Yu, J.G. Li, J.R. Zhao, et al [8] worked on the topic of "An experimental study of kerosene combustion in a supersonic model combustor using effervescent atomization", and their findings are -The smaller kerosene droplet having higher combustion efficiency. A local high temperature radical pool in the cavity is crucial in promoting the initiation and the subsequent flame holding of the kerosene combustion in a supersonic combustor.…”
Section: Fig-15 Central Pylon Injectormentioning
confidence: 99%